ESTIMASI DISTRIBUSI BERAT SAYAP DAN DISTRIBUSI LIFT UNTUK OPTIMASI BENDING MOMENT DENGAN SISTEM FUEL TRANSFER PADA PESAWAT BOEING 737-500 - Arifin, Mufti; Yuniarti, Endah; Sari, Rafika Arum; Said, Ahmad Akmal (JTK: JURNAL TEKNOLOGI KEDIRGANTARAAN, 2019)
Aside from being a manufacturer of lift force, a wing is functioning hold the load that occurs in the structure of the aircraft, such as the shear load, twist and bending. Of all the load the load bending is the greatest burden are received by the wings. Setting the load bending is one of the major factors in reducing the burden experienced by the wing. However, the optimal value indicated opposite between on land and in the air, to take advantage of the situation to use fuel system transfers the load alleviation. Fuel transfer load alleviation is a system that automatically move the fuel more in the tank at the time in part on land and are on the outside of the tank at the time in the air so that the effect of the load bending bending loads can be reduced, which generated as the result of addition between the weight distribution and the distribution of lift that occurs on the wings so as to calculate the bending data needed weight distribution and the distribution of lift on the wing. This research aims to know the weight distribution occurs on the wings of the Boeing 737-500. The value of the weight distribution and distribution of lift yield optimization moment on two States namely, on land and in the air with three variations of the fuel transfer that is, constant with a value of 40134.53 N, linear with a value of 48059.53 N, and the maximum value of 172386.50 N.